Practices and Debates of Digital Human Rights Activism Across Nations (Universitas Terbuka, 2025)
This study explores the ongoing debate about human rights as both a concept of social movement and a legal, institutional entity requiring organizations. The rise of digital media creates opportunities for collaboration between various stakeholders, allowing them to focus on the ultimate goal of activism: social change. We analyze the debates and implementation of digital activism related to human rights issues through a systematic literature review of 38 articles. The literature presents an ongoing debate between two conceptualizations of human rights: one as a social movement and the other as institutionalized within formal structures. This debate has implications for understanding the dynamics between organizational repertoires of activism and grassroots digital movements, particularly regarding the role of online contention. A mapping of the period from 2006 to 2023 reveals that citizen and local community initiatives more often drive digital activism than formal organizational campaigns. However, as the boundaries between these forms of activism increasingly blur, transnational collaborations encompassing NGOs and grassroots movements (including indigenous, diaspora, and citizen-led initiatives) have gained strength in digital activism. These developments suggest that sustained cooperation between organizational actors and grassroots movements is essential for achieving meaningful social change.